On-the-fly detection of a class of word-based patterns in labelled DAGs - Hurfin, Michel; Raynal, Michel (Zielona Góra: Uniwersytet Zielonogórski)
The problem tackled in this paper originates from the debugging of distributed applications. Execution of such an application can be modelled as a partially ordered set of process states. The debugging of control flows (sequences of process states) of these executions is based on satisfying the predicates by process states. A process state that satisfies a predicate inherits its label.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka